Prototype and scriptaculous : taking the pain out of JavaScript - Angus, Chris (O'Reilly short cuts., 2006)
JavaScript is carrying more and more programming load lately as Ajax has become popular. Scripting Ajax from scratch isn't much fun, but fortunately there are libraries to help. Prototype and Scriptaculous will let you get much more work done in much less time, automating tasks from processing XMLHTTP requests to creating animations that draw attention to your interfaces. This Short Cut demonstrates how to use Prototype for a wide range of tasks, including event handling, DOM processing, string and form process, and Ajax communications.